Anchovies (Stolephorus sp.) By-product Material as a Fish-feed Ingredient of Seurukan Fish (Osteochilus vittatus): Effect on Growth Performance and Gut Morphology - Ilham Zulfahmi; Anggi Audila; Ayu Nirmala Sari; Firman M Nur; Rudy Agung Nugroho; Iwan Hasri (Journal of Aquaculture and Fish Health, 2022)
Fish meal is an important part of raw material for fish feed. However, the use of fish meal is considered unsustainable, compete with human being and expensive. By product of Anchovy (Stolephorus sp.) which contains high protein is potential to be used to replace fish meal. Present study aimed to determine the utilization of anchovy by-products raw materials as feed ingredient for seurukan fish (Osteochilus vittatus) and evaluate its effect on the growth performance and intestinal morphology. In total 250 seurukan fish (initial weight 0.67 ± 0.01 g) was randomly divided into four triplicates groups: control group, and experimental diets which had different inclusion level of anchovy by-products meal: 50%, 35%, and 20%. Fish were fed with different diet at level of 8% of body weight three times a day for 28 days. Present results showed that the inclusion of anchovy by-product meal in the feed by 50% can produce a higher value of weight gain (0.47±0.02 g), length gain (0.69±0.09 cm), SGR (2.20±0.51%) and feed efficiency (77.89±3.71%) compared to control feed (p<0.05). There was no significant difference in the survival rate and gut length ratio among groups of seurukan fish. Meanwhile, the average villi length and villi width of the seurukan fish fed experimental groups increased significantly compared to the control group (p<0.05). In conclusion, the 50% anchovy by-products meal inclusion in the diet of seurukan fish is beneficial to enhance growth, feed efficiency and improved feed absorption as indicated by histological analysis.